Synergistic treatment of osteosarcoma with biomimetic nanoparticles transporting doxorubicin and siRNA - Zhao, Jingtong; Mu, Xupeng; Hou, Xuejia; Zhang, Xiaowen; Li, Ping; Jiang, Jinlan (Frontiers in Oncology, 2023)
Osteosarcoma is the most common malignant bone tumor in children and adolescents. Treatment usually requires surgical removal of all detectable cancerous tissue and multidrug chemotherapy; however, the prognosis for patients with unresectable or recurrent osteosarcoma is unfavorable. To make chemotherapy safer and more effective for osteosarcoma patients, biomimetic nanoparticles (NPs) camouflaged by mesenchymal stem cell membranes (MSCMs) were synthesized to induce apoptosis in osteosarcoma cells via codelivery of the anticancer drug doxorubicin (DOX) and a small interfering RNA (siRNA). Importantly, the NPs have high biocompatibility and tumor-homing ability. This study aimed to improve the efficacy of osteosarcoma therapy by using the synergistic combination of DOX and an siRNA targeting the apoptosis suppressor gene survivin. Methods: Biomimetic NPs (DOX/siSUR-PLGA@MSCM NPs) were synthesized by coloading DOX and siRNA-survivin (siSUR) into poly (DL-lactide-co-glycolide acid) (PLGA) by double emulsion solvent evaporation method. The NPs were camouflaged by MSCMs to deliver both DOX and the survivin-targeting siRNA. The nanoparticles were also characterized and evaluated for their cellular uptake ability, in vitro release ability, in vitro and in vivo antitumor effects, and biosafety. Results: DOX/siSUR-PLGA@MSCM NPs had good tumor-homing ability due to the membrane modification of the MSCs. The drug-laden biomimetic NPs had good antitumor effects in homozygous MG63 mice due to the synergistic effect of the drug combination. Conclusion: DOX/siSUR-PLGA@MSCM NPs can combine a chemotherapeutic drug with gene therapy to improve therapeutic effects in osteosarcoma patients based on the good tumor targeting and biosafety of the NPs.